Liver tissue engineering and cell sources: issues and challenges. (15th March 2013) - Palakkan, Anwar A.; Hay, David C.; PR, Anil K.; TV, Kumary; Ross, James A.
Abstract Liver diseases are of major concern as they now account for millions of deaths annually. As a result of the increased incidence of liver disease, many patients die on the transplant waiting list, before a donor organ becomes available. To meet the huge demand for donor liver, alternative approaches using liver tissue engineering principles are being actively pursued. Even though adult hepatocytes, the primary cells of the liver are most preferred for tissue engineering of liver, their limited availability, isolation from diseased organs, lack of in vitro propagation and deterioration of function acts as a major drawback to their use. Various approaches have been taken to prevent the functional deterioration of hepatocytes including the provision of an adequate extracellular matrix and co‐culture with non‐parenchymal cells of liver. Great progress has also been made to differentiate human stem cells to hepatocytes and to use them for liver tissue engineering applications. This review provides an overview of recent challenges, issues and cell sources with regard to liver tissue engineering.